Dinâmica de produção de forrageiras anuais de inverno semeadas em diferentes épocas - Ferrazza, Jussara Maria (2011)
Forage production seasonality is a great concern in southwestern Brazil. It occurs mainly due to the low temperatures and frost that occur during the winter. Those characteristics prevent forage plants growth, causing lack forage shortage to herds. The trial was carried out from March to November 2009 in order to evaluate productive characteristics of winter annual forage grasses (Avena strigosa Schereb, Lolium multiflorum Lam, Avena sativa, Triticum aestivum, Secale cereale, and X Triticosecale Wittmack) under four sowing dates: March 11th, April 8th, May 6th and June 3rd. Completely randomized blocks with three replications in a split plot design was used. It was evaluated number of days to first harvest, number of harvests, pasture utilization period, tiller and plant population densities, total herbage production, stubble mass, herbage production by harvest, and production dynamics (dry matter accumulation rate). There was significant interaction between grasses and sowing dates for all variables, indicating many combinations between forage species and sowing date according each system. White oats, ryegrasses and black oat cv. IAPAR 61 performed better in relation to forage production and forage production persistance, especially if sown until early May. In relation to accumulation rate, white oats UTF Iguaçú and IPR 126, black oat IAPAR 61, ryegrasses, and rye presented better performance, which presented average of 51.4 kg DM ha-1 after first cut, showing a great performance in terms of forage production and maintenance of their forage production, especially when sowed until beginning May.